Customer service in libraries : (The Scarecrow Press, Inc., 2013)
In this book, nine librarians from across the country describe their libraries' best practices in this key area. Their contributions range from all encompassing customer service policies and models any library can both adapt and be proud of to micro-approaches that emphasize offering excellent user focused technology planning, picture book arrangement with patrons in mind, Web 2.0 tools to connect users with the library, establishing good service delivery chains, and making your library fantastic for homeschoolers. As past Public Library Association President Audra Caplan writes in her introduction to this book, "There is nothing magical about providing excellent customer service; it just takes the right people, the right philosophy and the passion to make it a reality." If you have got all that, here in this book are the best practices to make stellar customer service a reality for your library's users